Risk of ARI among Non-exclusively Breastfed Under-Five Passive Smoker Children: A Hospital-Based Cross-sectional Study of Nepal - Thapa, Pushpa; Pandey, Achyut Raj; Dhungana, Raja Ram; Bista, Bihungum; Thapa, Barsha; Mishra, Shiva Raj (Frontiers in Public Health, 2016)
Background: As Nepal witnesses high burden of both acute respiratory infection and passive smoking among under-five children, studies on effect modification of exclusive breast feeding on passive smoking and acute respiratory infection carry huge significance. With Nepal holding no evidence in this regard, findings would be useful to promote a cost-effective intervention: exclusive breastfeeding. This study was therefore conceived as an effort to bring to light the modifying effect that exclusive breastfeeding may have on the association between passive smoking and acute respiratory infection among under-five children. Methods: One hundred and ninety eight parents of under-five children from Kanti Children's Hospital, Kathmandu, Nepal participated in this descriptive, cross-sectional study carried out in October, 2012. Data collected from a semi-structured questionnaire were subjected to univariate, bivariate, and multivariable analysis in R version 3.1.2. Results: Non-exclusively breastfed children with presence of anyone smoking at their house (aOR=4.8, 95% CI: 1.7-13.2) and smoking in presence of children (aOR=6.4, 95% CI: 1.1-38.3) had higher chances of acute respiratory infection, nevertheless this remained insignificant among the exclusively breastfed ones. Having a separate kitchen in the house showed protective effect against acute respiratory infection among exclusively breastfed children (aOR=0.2, 95% CI: 0.1-0.6). Children whose mothers spent at least two hours per day in the kitchen had a higher chance of developing acute respiratory infection, regardless of being exclusively breastfed (aOR= 4.5, 95% CI: 1.5-13.1) or non-exclusively breastfed (aOR= 4.5, 95% CI: 1.4-14.2) compared to those who spent less than two hours per day. Conclusions: Non-exclusive breastfeeding may increase the chances of deleterious effects of household passive smoking like acute respiratory infection among under-five children. As these findings are not conclusive, studies with better design and larger samples are warranted to confirm the effect. Keywords: Acute respiratory infection; Cross-sectional study; Exclusive breastfeeding; Household passive smoking; Nepal; Under-five children